Cervico vaginal prolapse correction and management by using bilateral configuration of sterile synthetic plastic materials in local breed cow - Jiregna Dugassa Kitessa; Kisi Bekele Terefe (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Background: Cervico vaginal prolapsed is one of the most common disorders of the reproductive organs at the end of pregnancy and rarely after. Objective: Description of the surgical management of cervico vaginal prolapsed in normal delivery. Animals: Emaciated, local breed cow that was kept under an extensive management system. Study design: Case report  Study methods: Patient history and clinical findings, diagnosis, treatment  Outcomes: After frequent follow up and well provision of post operative care, the patient was recovered. Conclusion: Cervical-vaginal prolapsed can lead to infertility and sterility unless it is treated early, before it worsens. The use of sterile rectangular plastic material to prevent recurrence on the bilateral sides of the vulvar lips together with adequate sutures appears promising and is highly recommended for similar cases.